2023
DOI: 10.1159/000528144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hysterotomy Closure Technique on Subsequent Cesarean Scar Defects Formation: A Systematic Review

Abstract: Introduction: The uterine caesarean scar defect, also known as uterine niche or isthmocele, is an irregularity in the anterior uterine wall at the site of a previous cesarean section scar. It is associated with obstetrical complications such as caesarean scar ectopic pregnancy, uterine rupture and, the placental accreta spectrum. Women with cesarean scar defects are frequently asymptomatic, but they may also experience abnormal vaginal bleeding, chronic pelvic pain, and infertility. Methods: This systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, in our opinion, it is not right that the authors concluded that "double-layer closure ensures a better healing process of the uterine incision" when no pooling of data has taken place. As far as we are aware, no quantitative data support the statement of Genovese et al [1] that double-layer closure after CS is superior to singlelayer closure. The fact that several guidelines recommend a specific suture technique is, in our opinion, no reason to not further elaborate on this comparison: the NICE guideline has been updated in March 2021 and now states "as there was no difference between single and double layer closure for the majority of outcomes, the committee agreed that either technique could be used" [3].…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…However, in our opinion, it is not right that the authors concluded that "double-layer closure ensures a better healing process of the uterine incision" when no pooling of data has taken place. As far as we are aware, no quantitative data support the statement of Genovese et al [1] that double-layer closure after CS is superior to singlelayer closure. The fact that several guidelines recommend a specific suture technique is, in our opinion, no reason to not further elaborate on this comparison: the NICE guideline has been updated in March 2021 and now states "as there was no difference between single and double layer closure for the majority of outcomes, the committee agreed that either technique could be used" [3].…”
mentioning
confidence: 55%
“…Although the hypothesis of our clinical trial was also that double-layer uterine closure could reduce niche prevalence and related symptoms, based on our systematic review and meta-analysis [12], we did not prove this in our large RCT the "2Close study" [11]. As stated in Table 2 in the article of Genovese et al [1], we found a small difference in niche prevalence in favour of singlelayer closure. All other short-term outcomes, including perioperative findings and ultrasound measurements after 3 months, as well as bleeding disorders and quality of life at 9 months follow-up, were not different.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Studies have demonstrated that the use of long-lasting absorbable sutures, such as poliglecaprone or polydioxanone thread, appears to reduce the risk of developing an isthmocele compared to the use of rapidly absorbable sutures [39,40]. A recent systematic review conducted by Genovese et al [41] analyzed a total of six studies and concluded that closing the hysterotomy with a continuous double-layer suture technique would therefore be a suitable option to prevent the formation of cesarean scar defects. Specifically, the first layer should encompass the decidua, and the second layer should overlap the first.…”
Section: Uterine Suturing Techniquementioning
confidence: 99%